Exertion and pain do not alter coordination variability in runners with iliotibial band syndrome - Hafer, J. F.; Brown, A. M.; Boyer, K. A. (Clinical Biomechanics, 2017)
Background: Iliotibial band syndrome is a common overuse running injury which results in altered mechanics. While injuries alter discrete mechanics, they may also cause a change in coordination variability, the stride-to-stride organization of runners' movement patterns. Uninjured and injured runners may experience a change in coordination variability during a run to exertion due to fatigue, pain, or a combination of these factors. The aim of the current study was to determine if runners with iliotibial band syndrome and uninjured runners display different segment coordination variability across the course of a run to exertion. Methods: 3D kinematics were collected as 13 uninjured runners and 12 runners with iliotibial band syndrome ran on a treadmill. A modified vector coding technique was used to calculate coordination variability during stance for segment couples of interest. Coordination variability was compared between uninjured and injured runners at the beginning and end of the run. The influence of pain on coordination variability was also examined. Findings: There were no differences in coordination variability at the beginning or end of the run between uninjured runners and those with iliotibial band syndrome. The change in coordination variability due to the run was not different between uninjured runners, injured runners who experienced no change in pain, and injured runners who did experience a change in pain. Interpretation: Runners do not constrain the patterns of segment motion they use in response to exertion nor does it appear that occurrence of pain during running results in a differential change in coordination variability.